Nuclear factor of activated T-cells 5 is indispensable for a balanced adaptive transcriptional response of lung endothelial cells to hypoxia - Laban, Hebatullah; Siegmund, Sophia; Schlereth, Katharina; Trogisch, Felix; Ablieh, Alia; Brandenburg, Lennart; Weigert, Andreas; Torre, Carolina de la; Mogler, Carolin; Hecker, Markus; Kuebler, Wolfgang M; Korff, Thomas (Cardiovascular research, 2024)
Chronic hypoxia causes detrimental structural alterations in the lung, which may cause pulmonary hypertension and are partially mediated by the endothelium. While its relevance for the development of hypoxia-associated lung diseases is well known, determinants controlling the initial adaptation of the lung endothelium to hypoxia remain largely unexplored.We revealed that hypoxia activates the transcription factor nuclear factor of activated T-cells 5 (NFAT5) and studied its regulatory function in murine lung endothelial cells (MLECs). EC-specific knockout of Nfat5 (Nfat5(EC)−/−) in mice exposed to normobaric hypoxia (10% O2) for 21 days promoted vascular fibrosis and aggravated the increase in pulmonary right ventricular systolic pressure as well as right ventricular dysfunction as compared with control mice. Microarray- and single-cell RNA-sequencing-based analyses revealed an impaired growth factor-, energy-, and protein-metabolism-associated gene expression in Nfat5-deficient MLEC after exposure to hypoxia for 7 days. Specifically, loss of NFAT5 boosted the expression and release of platelet-derived growth factor B (Pdgfb)—a hypoxia-inducible factor 1 alpha (HIF1α)-regulated driver of vascular smooth muscle cell (VSMC) growth—in capillary MLEC of hypoxia-exposed Nfat5(EC)−/− mice, which was accompanied by intensified VSMC coverage of distal pulmonary arteries.Collectively, our study shows that early and transient subpopulation-specific responses of MLEC to hypoxia may determine the degree of organ dysfunction in later stages. In this context, NFAT5 acts as a protective transcription factor required to rapidly adjust the endothelial transcriptome to cope with hypoxia. Specifically, NFAT5 restricts HIF1α-mediated Pdgfb expression and consequently limits muscularization and resistance of the pulmonary vasculature.